Association of BoLA-DRB3.2 alleles with tick (Boophilus microplus) resistance in cattle - Martinez, M.L; Machado, M.A; Nascimento, C.S; Silva, M.V.G.B; Teodoro, R.L; Furlong, J; Prata, M.C.A; Campos, A.L; Guimaraes, M.F.M; Azevedo, A.L.S (Genetics and molecular research, 2006)
Losses caused by bovine tick burdens in tropical countries have a tremendous economic impact on production systems. Besides reducing production, this parasite can cause death in the most susceptible animals. The use of commercial acaricides has been the major method of control, but their misuse has led to tick resistance to many chemicals. More recently, vaccines have been used in some countries without solving the problem completely. An alternative could be the development of resistant animals and the use of genetic markers and candidate genes that could help with the enormous task of selecting resistant animals. The bovine lymphocyte antigen genes (BoLA) have been shown to be associated with some parasitic infestations and disease incidence. Thus, the objective of the present study was to determine the association of BoLA-DRB3.2 alleles with tick resistance in cattle. The study was conducted on 231 F2 (Gyr x Holstein) animals that were artificially infested with 10,000 tick larvae. Log of tick count +1 was used as the dependent variable in a mixed animal model with allele substitution effects in addition to fixed effects of year and season at tick count, sex of calves, age of animal at tick count, hair type (short-straight, short-curl, long-straight, and long-curl), coat color (white, >75% white, 50- 75% white, and 25-50% white), and additive genetic, permanent environmental and residual effects as random. Females showed fewer ticks than males. Animals with short-straight hair were more resistant to tick infestation than animals with long-curl hair, and animals with whiter coat color also had fewer ticks. An association between BoLA alleles and lower tick number was found for alleles DRB3.2 *18, *20 and *27 at the 5% significance level. Also, one allele (DRB3.2*16) showed an association at the 10% level. Allele *27 was the most frequent in the population (30.7%), followed by alleles *16 (10.8%), *20 (8.7%) and *18 (2.4%). These results suggest that BoLA-DRB3.2 alleles could be used to help in the selection of animals resistant to tick infestation. However, further studies involving a larger population of cattle in combination with other BoLA genes may help to understand the mechanisms of resistance to parasites.